Effect of illumination on negative linear expansion of TlGaSe2 layered crystals - Seyidov, MirHasan Yu; Suleymanov, Rauf A.; Yakar, Emin; Abdullayev, N. A.; Mammadov, T. G. (Pergamon-Elsevier Science Ltd, 2008)
Effect of illumination on negative thermal expansion of TlGaSe2 crystals has been investigated. Strong trasformation of negative linear expansion coefficient has been observed after the illuminations. It is supposed that two main mechanisms are responsible for observed effect: formation of photoelectret states and reverse piezoelectric effect. The electronic nature of negative linear expansion of TlGaSe2 crystals has been proved for the first time. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Semiconductors; Ferroelectricity; Thermal expansion; Piezoelectricity